The unplanned teenage pregnancy - S.M. Ross (Curationis, 1979)
Surveys conducted in the Durban area of Natal showed that 18 per cent of all pregnancies occurred amongst teenagers with the incidence amongst the various population groups varying bëtween Whites 14 per cent, Indians 17 per cent, Coloureds and Blacks 20 per cent. This compares with a world-wide teenage pregnancy rate of 10-15 per cent. Amongst primigravid pregnancies 33 per cent Indians and 53 per cent of Africans were found to be 18 years of age or less.